Antifungal properties of Piper sarmentosum leaf extracts against Trichophyton rubrum and Malassezia furfur - Nurul 'Adani Sanusi
T. rubrum and Malassezia furfur are common fungal pathogens causing skin infections. In immunocompromised patients, these fungi have been reported to cause widespread and invasive infections. Treatment with currently available antifungal agents may lead to unfavourable side effects and the emergence of resistant strains. Piper sarmentosum or locally known as kaduk has been reported to have antibacterial and antifungal properties. However, to date, its antifungal properties against these fungi have not been extensively reported. The objective of this study is to evaluate the antifungal properties of P. sarmentosum leaf extracts against these fungi. Three different solvents were used to extract the P. sarmentosum leaves. The solvents were n-Hexanc (non-polar), dichlorornethane (semi-polar), and ethanol (polar). Antifungal properties of the extracts were determined by the disc diffusion and broth dilution methods. The inhibition zone was measured and the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) were determined. Total phenolic acids and flavonoids contents were estimated by Folin-Ciocalteu and colorimetric assay respectively. The morphological changes of the treated fungi ware observed under a Scanning Electron Microscope (SEM). The correlation between antifungal properties of the compound content of the extracts also determined. All types of extracts have exhibited antifungal properties against T. rubrum and M. furfur furfur. Among the extracts, dichloromethane leaf extract has demonstrated the highest antifungal properties whereby at the concentration of S mg/mL, it has started to show signs of inhibition indicated by the presence of inhibition zone with the diameter of 6.67± I. IS rnm for T. rubrum and 6.67±0.S8 rnrn for M. furfur. These results were in line with the MIC and MFC results where the dichlorornethane leaf extract exhibited the lowest MIC (S mg/mL) and MFC (10 mg/rnl.) for both fungi. Dichlorornethane leaf extract also showed the highest total phenolic acids (S.3S mg GAE/g) andjlavonoicl (9.S0 mg CE/g contents. Based on the correlation study, there was a positive correlation between antifungal properties of the extracts and their TPC and TFC values. Morphological study using SEM showed significant structural changes of the treated fungi. P. sarmentosum leaf extracts exhibited antifungal properties against T. rubrum and M. furfur. Their antifungal properties were correlated with the presence of phenolic acids and flavonoids. This result suggests that P. sarmentosum leaf extracts could potentially be used as an alternative therapeutic agent against T. rubrum and M.furfur infection.